Assessing pavement interfacial bonding condition. (15th October 2016) - Guo, Chengchao; Wang, Fuming; Zhong, Yanhui
Highlights: The modulus and interfacial bonding condition is an order on the deflection, and the strength and bonding condition take same effect on the structure deformation. With the interfacial friction coefficient decreasing, the deflection all increase, and the difference of interfacial radial stress gets larger. The interfacial friction coefficient has good relationship with the deflection basin index, and SCI/BCI and F1 /F2 can be used to reflect the interfacial bonding condition. Abstract: When analyzing the pavement structure, the interface condition is always supposed to be completely continuous, but it doesn't correspond to the reality. To deal with this situation and provide suggestions on pavement construction, the asphalt pavement will be studied further. Taking a practical project as an example, the mechanical response of the structure layer of asphalt pavement has been analyzed by finite element software ABAQUS with different interlayer friction coefficients. It shows that the interlayer friction coefficient has great influence on the surface deflection, the tensile stress at the bottom layer and the stress differences among radial stresses of the interface bonding position. Moreover, the deflection basin index has a good relationship with the interlayer friction coefficient. The relation between deflection basin index and interlayer friction coefficients is established, and a method of assessing the pavement interfacial bonding condition is suggested.